STRATEGI PROMOSI PARIWISATA KOTA KUPANG MELALUI PEMBUATAN MEDIA KATALOG WISATA - Abas Kasim; Antonio E.L. Nyoko; Juita L.D. Bessie (Universitas Nusa Cendana, 2017)
A Factor that hinder the development of tourism is mismanagement of tourism promotion and tourisminformation management system, so that reduce the tourists interest for sightseeing. In KupangCity, thecapital NTT Province, promotional tour has been done, however the media tourism catalog offer lessspecific information about tourist attractions (natural, historical, religious place), event, food, travel agencyand tourism facilities in Kupang City and less attractive with low quality graphics display. Therefore, itrequired to design of more attractive and informative City Tourism Catalog as a tourism promotion media.Based on the result of the SWOT Analysis, tourism catalog of Kupang is located on strategies quadrant ofthe Matrix Grand Strategy that support policies of aggressive (Growth Oriented Strategy). This research notonly produces the right strategy in the tourism promotion, but also produces a Kupang City’s tourismpromotion catalogue that complement existing tourism catalog. It will be a One Stop Information Mediathat more comprehensive developed with high-quality graphical display and presented in bilingual,Indonesia and English.Keywords : Tourism Catalogue, Tourism Promotion Strategy